KNOWLEDGE IMPROVEMENT RELATED TO HYPERTENSION - Tantri Puspita, Tantri Puspita; Muhammad Hadi Sulhan, Muhammad Hadi Sulhan; Sri Yekti Widadi, Sri Yekti Widadi; Andhika Lungguh Perceka, Andhika Lungguh Perceka; Wahyudin, Wahyudin; Gin Gin Sugih Permana, Gin Gin Sugih Permana (Jurnal Pengabdian Masyarakat DEDIKASI, 2024)
Hypertension remains a global health problem and contributes significantly to cardiovascular morbidity and mortality. This Community Service aims to increase knowledge and awareness about hypertension in the target population through education. Health education was designed to address common misconceptions surrounding hypertension. So that participants' knowledge increases so that they focus on lifestyle modification and risk factor management, as well as early detection of the risk of hypertension in participants. This Community Service was attended by 51 participants.Participants who attended ranged in age from teenagers to the elderly. The Community Service Committee collaborates with local stakeholders from preparation to implementation of activities and ending with closing. By improving technology by involving the community, it is hoped that hypertension management can reduce the burden of cardiovascular disease in society